Laryngeal cancer in two non-consanguineous people (spouses): a case report - L. G. Kozhanov; А. L. Kozhanov; Yu. Yu. Vyaltseva; А. V. Egorova; S. V. Chulkova (Опухоли головы и шеи, 2020)
The objective is to report a rare case of laryngeal cancer in spouses. Case report. A 59-year-old female patient was admitted to the Department of Head and Neck Tumors in December 2019 with complaints of hoarseness. In 1997, she had radiotherapy for T1N0M0 laryngeal cancer. After comprehensive examination, she was diagnosed with recurrent laryngeal cancer. The patient has undergone frontolateral laryngeal resection. A 67-year-old male patient was admitted to the Department of Head and Neck Tumors in November 2019 with T3N0M0 laryngeal cancer (diagnosed 2 months before). He has undergone extended frontolateral laryngeal resection followed by radiotherapy in the postoperative period. Discussion. Both patients had no risk factors, such as occupational hazards or smoking. However, both spouses had close relatives with cancer, what indicates their genetic predisposition to malignant tumors. The female patient was found to have human papilloma virus (HPV) in the tumor cells, whereas her spouse was HPV-negative, although rapid histology showed indirect signs of HPV, which does not exclude the elimination of HPV. Conclusion. In this rare case of laryngeal cancer diagnosed in two non-consanguineous spouses, the disease is likely to be caused by their hereditary predisposition, HPV infection, and the fact that they lived in the same socioeconomic conditions.